All Opinions Matter - Lloyd Rieber; Anne Marie Zimeri; Tong Li (Journal of the Scholarship of Teaching and Learning, 2022)
This paper describes a study, in the form of multiple field tests, designed to help students in an environmental health science course express and understand the subjective perspectives that they and their classmates hold on important course topics. This study is part of a project using the Q sorting technique found in Q methodology as the basis for a classroom activity, an approach we term Q pedagogy. Q methodology is a research methodology designed to study people’s subjectivity and was first formulated by William Stephenson in the 1930s. Results show that the Q pedagogy activity was effective in promoting individual reflection and group discussion among students in the class. Q pedagogy adapts the rich, mixed methods research approach of Q methodology for instruction to advance the Scholarship of Teaching and Learning (SoTL).